From Hegel, despite Hegel, but with Hegel:: decolonial philosophy as a practical-poietic method for the liberation of Latin America (Revista Eletrônica Estudos Hegelianos, 2024)
this paper examines the reception of Hegel’s philosophy in Latin American “decolonial philosophies” from the 1960s onwards, especially in Enrique Dussel’s philosophy of liberation, whose “presence of Hegel” (sometimes explicit, sometimes implicit) is essential for the substantiation of the “analetic method” in terms of “absolute principle” and “final proposal”, despite the inversions. To this end, the text is divided into three moments. The first examines the significant participation of Hegelian philosophy in the foundation of Latin American decolonial thought. The second moment examines the substantiation of Dussel’s analetical method as a philosophical proposal to overcome Hegelian dialectics in epistemological, ontological and historical terms. In the third moment, we compare the “absolute principle” and “final proposal” of Dussel’s “practical-poietic method” with the principles and purposes of Hegel’s “dialectic of liberation” and “poietic”. In the end, we conclude that the “decolonial turn” claimed above all by Dussel’s method cannot escape the Hegelian idea of “universal history” as the “self-production of absolute freedom” in terms of principle and final solution, despite the methodological inversions.